2013
DOI: 10.5005/jp-journals-10006-1227
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Placentation by Ultrasonography: A Simple Predictor of Preeclampsia

Abstract: Introduction: Preeclampsia is a disease of trophoblastic tissue. it is a complex clinical syndrome involving multiple organ systems and still remains the principle cause of maternal and perinatal morbidity and mortality. The search for an ideal predictive test is still on, and preventive measures for preeclampsia remain a challenging entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
8
17
1
Order By: Relevance
“…The results of present study are close to the study done by Bhalerao AV et al, who stated that ultrasonography in pregnant women during 20-24 weeks of gestation can be a ease, noninvasive, useful and cost-effective tool as a predictor ofpreeclampsia. 10 Futhermore, results are also comparable to the investigations done by Kakkar et al in which out of the total 150 women, 84 (56%) had laterally located placenta and of them, 56 (66.6%) developed preeclampsia, while the remaining 66 (44%) had centrally located placenta and of them, 24 (36.3%) developed preeclampsia.…”
Section: Discussionsupporting
confidence: 88%
“…The results of present study are close to the study done by Bhalerao AV et al, who stated that ultrasonography in pregnant women during 20-24 weeks of gestation can be a ease, noninvasive, useful and cost-effective tool as a predictor ofpreeclampsia. 10 Futhermore, results are also comparable to the investigations done by Kakkar et al in which out of the total 150 women, 84 (56%) had laterally located placenta and of them, 56 (66.6%) developed preeclampsia, while the remaining 66 (44%) had centrally located placenta and of them, 24 (36.3%) developed preeclampsia.…”
Section: Discussionsupporting
confidence: 88%
“…It is statistically significant (p value <0.001). Many of the other authors like Pai M et al, 1 Patel A et al, 2 Liberti et al, 8 Bhalerao et al, 9 Magann et al, 10 Kartika Devrajan et al, 11 also suggested that central placenta is more common. However various other studies found lateral placenta to be more common like Kofinas et al, 5 Liberti et al, 8 kakkar, and Elena contro et al 12 These differences may be due to differences in criteria defining central and lateral placenta.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Kofinas et al (1989) reported a relationship between the lateral location of the placenta and the development of preeclampsia and IUGR as well as abnormal resistive index of the uterine artery in lateral placentas, without respect to confounding factors, such as risk factors for development of preeclampsia (21). According to an important study done by Bhalerao et al during year 2013, ultrasound has been shown as a cost-effective method for prediction of the development of preeclampsia (16), yet in this recent study, statistical analysis of lateral placentas in cases with underlying diseases and older mothers were not apparent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have revealed side-to-side differences in uteroplacental Doppler flow in pregnancies with unilateral placentas as well as the relationship between abnormal Doppler measurements and pre-eclampsia (13)(14)(15)(16)(17)(18)(19)(20)(21). However, reports on the direct association between placental location and development of pre-eclampsia, regardless of confounding factors (22), are limited.…”
Section: Introductionmentioning
confidence: 99%